PRIDE AND DIGNITY OF ADOLPHUS SIMPSON AS REVEALED IN POE’S THE SPECTACLES - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2023)
This research presents a description of the character and personality of Simpson in "The Spectacles." In conducting this research, the writer used qualitative research, in which the data are collected in the form of words and the writer is the key instrument. The data were collected from the short story, which was the primary source. The other books concerning theory, critics, statements, and notes on literature are secondary sources. The writer uses an objective approach in analyzing the data. The result shows that Simpson is pictured as a young, handsome, and romantic man, but he also has a real problem with his eyes. The traits of Simpson that appear most strikingly in the story are pride and dignity. Spectacles or glasses are a symbol of Simpson’s weakness. Furthermore, his spectacles are what make him dignified and proud. Simpson appears dignified and proud, but he could actually be a coward. Actually, he only cares about outward appearance. The sense of both dignity and pride is, of course, honorable. But in the short story, The Spectacles, the sense of dignity and pride is the weakness of one’s moral value. Outward appearances such as beauty, handsomeness, luxury wears or expensive dresses, wealth, a successful career, a famous reputation, high class or top rank in society, and a degree or academic title all portray pride and dignity. But in the short story, The Spectacles, Simpson displays misplaced pride and dignity. Madame Lalande is a wise and intelligent old lady. She remembers her wise mother and grandmother the most.